Simplify (2x+3)(x+4)
Answers
Answered by
3
Hi!!!!!
Here is the answer!!!!--------
=(2x+3)(x+4)
=2x(x+4)+3(x+4)
=2x^2+8x+3x+12
=2x^2+11x+12
Hope it hlpzzz!!!!!!
FOLLOW ME.....
Here is the answer!!!!--------
=(2x+3)(x+4)
=2x(x+4)+3(x+4)
=2x^2+8x+3x+12
=2x^2+11x+12
Hope it hlpzzz!!!!!!
FOLLOW ME.....
Answered by
2
hope it helps I Think it is correct
Attachments:
![](https://hi-static.z-dn.net/files/df3/6c5f189f6a2453f1dd19d2c20d212b0c.jpg)
Similar questions
Political Science,
9 months ago
Physics,
9 months ago
History,
9 months ago
Social Sciences,
1 year ago
English,
1 year ago
2x(x+4)−3(x+4)
Apply the distributive property.
2xx+2x⋅4−3(x+4)
Apply the distributive property.
2xx+2x⋅4+(−3x−3⋅4)
Remove parentheses.
2xx+2x⋅4−3x−3⋅4